Dare to be Different: Life Experience Narrative of BTEC Best Graduate - Jang, Johan; Pramono, Rudy; Purnamasari, Dian; Akuba, Stefy Falentino (Dinamika Pendidikan, 2020)
The aims of this research explained how the past, present, and future thoughts help to form the decision of an alumnus is still nineteen years old in explored a hobby and dreamed of becoming an entrepreneur. From interviews and analyses made, information gathered shows that the interviewee's past has generated confidence, independence and a sense of responsibility that contribute to the decision. The current situation experienced by the interviewee which is full support from parents and the ability to think rationality about her plan, enables her to make this decision. The interviewee also viewed her future with an acceptable plan supported by her family business as the last resort if her plan cannot be fruitful. This research opens an opportunity for stakeholders in the education field to understand and interpret this unorthodox life story wisely.